2021
DOI: 10.3390/plants10091951
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate Induction and Resistance to the Cabbage Moth, Mamestra brassicae, Differs among Kale Genotypes with High and Low Content of Sinigrin and Glucobrassicin

Abstract: The cabbage moth, Mamestra brassicae L. (Lepidoptera: Noctuidae), is a generalist insect pest of cruciferous crops. We tested glucosinolate induction by jasmonic acid (JA) and salicylic acid (SA), and by these phytohormones combined with feeding by M. brassicae larvae in four genotypes of kale, Brassica oleracea L. var. acephala (Brassicaceae). The genotypes tested had high glucobrassicin (genotype HGBS), low glucobrassicin (genotype LGBS), high sinigrin (genotype HSIN), and low sinigrin content (genotype LSIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…Hence, any change in the feeding preference of larva under the same conditions could be attributed to the differential chemical composition of the plant. Earlier reports have been shown that M. brassicae preference and performance are both affected by GSLs content and composition when comparing genotypes in choice and non-choice feeding experiments (Cartea et al, 2010;Jeschke et al, 2017;Badenes-Pérez and Cartea, 2021). However, how wounding and time-ofday may prime the plant to influence herbivore performance has not been previously reported.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, any change in the feeding preference of larva under the same conditions could be attributed to the differential chemical composition of the plant. Earlier reports have been shown that M. brassicae preference and performance are both affected by GSLs content and composition when comparing genotypes in choice and non-choice feeding experiments (Cartea et al, 2010;Jeschke et al, 2017;Badenes-Pérez and Cartea, 2021). However, how wounding and time-ofday may prime the plant to influence herbivore performance has not been previously reported.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that JA plays a crucial role in plant resistance to biotic stress. The JA content and related gene expression were significantly induced after insect feeding: JA was significantly increased by aphid‐induced or chewing herbivores in sweet pepper plants 50 and exogenous spraying of JA also increased plant resistance to insects. The weight gain of Mamestra brassicae larvae fed on JA‐treated plants was less than for larvae fed water‐treated plants 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some insects have developed strategies to overcome the toxicity of the glucosinolate–myrosinase system (Winde and Wittstock 2011 ), high concentrations of total GSL can affect even specialist insects and this may result in plant resistance (Hopkins et al 2009 ; Björkman et al 2011 ). GSL levels can be induced by herbivore damage, mainly by chewing insects which increase jasmonic acid levels in the plant, having positive or negative effects on subsequent herbivory (Bartlet et al 1999 ; Ponzio et al 2017 ; Badenes-Pérez 2021 ). As many glucosinolates and isothiocyanates are released upon tissue damage by the glucosinolate–myrosinase system chewing insects are more affected compared to phloem-sucking insects.…”
Section: Breeding Targets Conferring Insect Resistancementioning
confidence: 99%